AN ANALYSIS OF AN INNOVATION E-LEARNING ON MODERN PLATFORM - Murti Bandung; Muhammad Fauzan Rifani; Yustina Fitriani (INOVISH JOURNAL, 2020)
The development of technology has resulted in many innovations, one of which is in the field of education. Innovation in the field of education today apparently uses online learning systems, online tutoring course is one of the learning systems that make students or else easier to access knowledge anytime and anywhere. One of the E-learning innovations in online learning is an application called Ruangguru. Online study or online tutoring from Ruangguru is the highest number of students who have registered in Indonesia. Education in these days was no longer centered upon a back and forth between student and teacher; todays took on a more networked approach and student having their own direct connection for gain knowledge or information. This encouraged the development of a more personalized way of learning where a student’s independence and various way to gain knowledge. This study aims to analyze innovation e-learning on modern platforms in the development of learning medium Ruangguru.